The impact of carotid artery disease on outcomes of patients undergoing coronary artery bypass grafting - Abbaszadeh,Monir (2011)
OBJECTIVE: Although the overall complication rate has been decreased significantly in recent years, stroke is a severe complication after coronary bypass operations. The purpose of this study is to evaluate the influence of carotid artery disease on the results of patients under CABG operation. METHODS: In a retrospective cohort study, 1,978 patients under CABG operation were studied in Shariati Hospital between April 2002 and March 2006. The patients who had only valve replacement or non-CABG procedure were excluded from this study. As part of preoperative evaluation, carotid duplex ultrasonography scans were performed. In order to estimate the degree of carotid arteries stenosis, ultrasound imaging measurement and velocity criteria were considered. The patients were classified into three groups: those with no significant stenosis of the internal carotid artery (ICA) (moderate) group A, those with significant stenosis (sever) group B and those with the occluded ICA (critical) group C. Finally, all data were analyzed by SPSS software. Statistical analyses were performed using the following testes; chi-square, Fisher exact and Student's t tests. RESULTS: The distribution of the 1,978 patients undergoing CABG operation were as follows: group A = 1,938, group B = 30, and group C = 10. The results of the evaluations show that perioperative stroke rates were 1.2% (24 patients) in group A, 0.4% (eight patients) in group B and 0.3% (six patients) in group C (P<0.0001). Furthermore, perioperative mortality rates for groups A, B and C were 0.1% (two patients), 0.3% (five patients) and 0.4% (seven patients), respectively (P<0.0001). CONCLUSION: The stroke and mortality in patients undergoing CABG are increased when ICA occlusion is present.